Traductological Analysis of Culturemes in One Hundred Years of Solitude: Equivalencia y técnicas de traducción (2019)
This article presents a mixed focus analysis about the treatment of culturemes in the English translation of the novel One Hundred Years of Solitude. The culturemes,extracted by means of a double corpus, were classified in cultural fields, the translationtechniques were also identified, and the types and ranges of equivalence were determined through the Dynamic Traductological Mode (MDT, by its acronym in Spanish). The pro - duct of this research contributes to the consolidation and acceptance of the term culture- me in the traductology ́s topic and also demonstrates that the integration of two theore - tical and methodological proposals, such as translation with linguistic-textual orientation and the cultural current of functionalism, is useful for the development of an instrument for analyzing culturemes in literary works